Necesidad de reformar el artículo 570 del Código Orgánico Integral Penal para que los jueces y juezas de violencia contra la mujer y familia asuman la competencia en el juzgamiento de los delitos de violencia contra la mujer e intrafamiliar, a fin de impedir la impunidad de los mismos - Martínez Alvarado, Lita Alexandra (2015)
Our Constitution of the Republic gives a high-priority treatment to considered vulnerable groups as they are it the girls, children and adolescents, pregnant women, people of the third age, at the same time it guarantees a life free of violence in the public and private environment for what" will adopt (.) the necessary measures to prevent, to eliminate and to sanction all form of violence especially the one exercised against the women, girls, children and adolescents, mature bigger people, people with and against all person in disadvantage situation or vulnerability (.) ", it means it that the State has among its priorities to avoid the violence against the woman, in fact for the alarming growth of violence against Situation that he/she has forced that in the elaboration of the recent Code Penal (COIP) Organic Integral, have taken these aspects inside the crimes against the rights of freedom and there are them to him appropriately, so that they can be sanction object, like a protection form to the woman. The competent organ to know of these crimes according to that settled down in the Code Penal Organic Integral, they are those and the Judges of Penal Guarantees, leaving that the Units of Violence created recently, be only, that is to say; that all the crimes of violence against the women enter for Prosecutor's office, affecting the immediate emission of protection measures and the agile answer of the Justice in front of this type of of the Human rights. Situation that thwarts the constitutional spirit that guarantees the effective access to the justice to the women and members of the family, with special and expedite procedures, because although it is certain that the crimes so much in the Penal Code, inside the chapter second of the Code Penal Organic Integral, they are common crimes, they are not it their victims, but rather they respond to a specific type and that the same as the case of the girls, children and adolescents, they require of a judicial specialized organ for their treatment. The different acts of violence impact in the public and private life of the inhabitants, they influence in the structure of the family and in the woman's situation and the children and what is more serious has still qualified them to him as endemic, since we have them in all moment and place "the impunity it is in the whole continent, the violence against the women is, in the "small" aggressions and the impunity of those who don't complete their functions and obligations, what the aggressor's power increases and it allows him/her to arrive until the murder